2018
DOI: 10.1021/jacs.8b07485
|View full text |Cite
|
Sign up to set email alerts
|

Two-Fold C−H/C−H Cross-Coupling Using RhCl3·3H2O as the Catalyst: Direct Fusion of N-(Hetero)arylimidazolium Salts and (Hetero)arenes

Abstract: [Cp*RhCl] is the most prevailing catalyst employed for rhodium-catalyzed chelation-assisted C-H/C-H cross-coupling reactions due to the special ligand effect of Cp*. In this article, a novel concept of using a simple inorganic rhodium salt, RhCl·3HO, as the catalyst by taking advantage of in situ π-coordination to Rh with a (hetero)aromatic reaction component to stabilize Rh intermediates is proposed and evaluated. Our studies not only prove the feasibility of this concept but also disclose a novel 2-fold C-H/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(18 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…Decomposition of M/NHC catalysts via C–NHC coupling was detected in Mizoroki–Heck 27 , 62 , 65 and Suzuki–Miyaura 66 couplings, in the oligomerizations of alkenes and alkynes, 67 – 70 in CH-functionalizations of heterocycles, 71 and in many other reactions. 23 , 25 The C–NHC coupling reactions accompanied by two-electron reduction of the metal center were observed experimentally for Pd II , 22 , 23 , 25 Ni II , 22 , 23 , 25 , 72 Ru II , 73 , 74 Rh III , 75 79 Fe III ( ref. 80 ) and Cu III ( ref.…”
Section: Organometallic Chemistry Behind the H–nhc C–nhc And X–nhc Cmentioning
confidence: 82%
“…Decomposition of M/NHC catalysts via C–NHC coupling was detected in Mizoroki–Heck 27 , 62 , 65 and Suzuki–Miyaura 66 couplings, in the oligomerizations of alkenes and alkynes, 67 – 70 in CH-functionalizations of heterocycles, 71 and in many other reactions. 23 , 25 The C–NHC coupling reactions accompanied by two-electron reduction of the metal center were observed experimentally for Pd II , 22 , 23 , 25 Ni II , 22 , 23 , 25 , 72 Ru II , 73 , 74 Rh III , 75 79 Fe III ( ref. 80 ) and Cu III ( ref.…”
Section: Organometallic Chemistry Behind the H–nhc C–nhc And X–nhc Cmentioning
confidence: 82%
“…RhCl 2 ] 2 by availing the in situ π-coordination of (hetero)aromatic reaction component to stabilize the orthometalated Rh intermediates (Scheme 35). [47] They have demonstrated the feasibility of this concept in 2-fold CÀ H/CÀ H cross-coupling reaction of N-(hetero)-arylimidazolium salts with various (hetero)arenes to access diverse beneficial heteroaromatic molecules. Notably, simple RhCl 3 • 3H 2 O performs better than the extensively used [(Cp*)RhCl 2 ] 2 in this reaction.…”
Section: Annulationsmentioning
confidence: 99%
“…A simple RhCl 3 ·H 2 O catalyst was employed for the CDC reaction of N -(hetero)-arylimidazolium salts with (hetero)arenes to obtain water-soluble and fluorescence-on planar polycyclic heteroaromatic molecules (Scheme 52c). 75 Comprehensive DFT computation and the control experiments suggested that the in situ heteroarene η 6 -coordination to Rh( iii ) center stabilises the organorhodium intermediates in this reaction, in a similar manner to [Cp*Rh( iii )] complexes. It was suggested to go through two cycles, the first cycle is a typical Rh( iii ) to Rh( i ) process while the second cycle involves an unprecedented Rh( i ) to Rh( iii ) to Rh( i ) process with the release of hydrogen.…”
Section: Cross-dehydrogenative Coupling Of Arenesmentioning
confidence: 79%